2016
DOI: 10.1002/anie.201606979
|View full text |Cite
|
Sign up to set email alerts
|

A Bis(silylene)‐Substituted ortho‐Carborane as a Superior Ligand in the Nickel‐Catalyzed Amination of Arenes

Abstract: The synthesis and structure of the first 1,2-bis(NHSi)-substituted ortho-carborane [(LSi:)C]2 B10 H10 (termed SiCCSi) is reported (NHSi=N-heterocyclic silylene; L=PhC(NtBu)2 ). Its suitability to serve as a reliable bis(silylene) chelating ligand for transition metals is demonstrated by the formation of [SiCCSi]NiBr2 and [SiCCSi]Ni(CO)2 complexes. The CO stretching vibration modes of the latter indicate that the Si(II) atoms in the SiCCSi ligand are even stronger σ donors than the P(III) atoms in phosphines an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
90
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 151 publications
(93 citation statements)
references
References 82 publications
0
90
0
3
Order By: Relevance
“…[2,3] Additionally,i th as been recently found that some silylenes, particularly those stabilized by donor groups,h ave as tronger electron-donor capacity than the most basic phosphanes and even N-heterocyclic carbenes (NHCs). [4,5] This is ak ey factor of their newly reported behavior as steering ligands in homogeneous catalysis, [3,4] but, despite their strong nucleophilicity, the use of silylenes as nucleophiles for the formation of SiÀCbonds is still little developed. [1a,f,k, 6] Within the family of donor-stabilized silylenes,t hose having an amidinato fragment are being increasingly used because their syntheses are relatively easy and their electronic and steric properties can be easily tuned.…”
mentioning
confidence: 99%
“…[2,3] Additionally,i th as been recently found that some silylenes, particularly those stabilized by donor groups,h ave as tronger electron-donor capacity than the most basic phosphanes and even N-heterocyclic carbenes (NHCs). [4,5] This is ak ey factor of their newly reported behavior as steering ligands in homogeneous catalysis, [3,4] but, despite their strong nucleophilicity, the use of silylenes as nucleophiles for the formation of SiÀCbonds is still little developed. [1a,f,k, 6] Within the family of donor-stabilized silylenes,t hose having an amidinato fragment are being increasingly used because their syntheses are relatively easy and their electronic and steric properties can be easily tuned.…”
mentioning
confidence: 99%
“…[12] Thee lectronic structure of 1 was investigated by density functional theory (DFT) calculations,performed at the BP86/TZP level using the ADF software suite (see Supporting Information). The 29 Si NMR resonance of 1 is observed at d = 13.3 ppm, akin to the value observed for an ocarborane bridged bis-NHSi ligand.…”
mentioning
confidence: 99%
“…Since the first report on an NHSi used in metal‐mediated catalysis in 2001, various types of NHSi ligands (e.g., monodentate A , bidentate B , and tridentate pincer‐type ligand C , see Scheme ) as donor ligands towards transition‐metals (TM) have been described . As it turned out NHSi ligands can facilitate catalytic transformations owing to their excellent control over the electronic properties of TMs in the scaffolds mainly by taking advantage of the strong σ donor ability of Si II which lowers the activation barriers of the rate limiting steps at the TM active site (e.g., oxidative addition) . Most notable, NHSi ligands can initiate cooperative effects as shown in a heterobimetallic NHSi→Ni/Cu‐catalyzed Sonogashira coupling, NHSi→Fe catalyzed hydrosilylation of ketones and NHSi→Ni catalyzed hydrogenation of olefins .…”
Section: Methodsmentioning
confidence: 99%